DEVELOPMENT AND OPTIMIZATION OF MESOPOROUS SILICA NANOPARTICLES LOADED WITH ADIANTUM PHILIPPINES FRACTION AND THUJA OIL AS A POTENTIAL WOUND HEALING AGENT - PAGAR, SWATI A.; THOMBRE, NILIMA A. (International Journal of Applied Pharmaceutics, 2026)
Objective: This study aimed to develop and optimize mesoporous silica nanoparticles (MSNs) loaded with Adiantum Philippines chloroform fraction and Thuja occidentalis essential oil for enhanced wound healing applications, addressing the clinical need for improved topical therapeutic delivery systems. Methods: MSNs were synthesized using the sol-gel method and optimized through box-behnken factorial design with three variables: CTAB concentration (1-3g), TEOS volume (8-16 ml), and stirring time (1-4h). Seventeen formulations were evaluated for particle size, zeta potential, and entrapment efficiency. The optimized formulation was characterized using FTIR, DSC, SEM, and DLS, followed by in vitro drug release and stability studies. Wound healing efficacy was assessed using full-thickness excision wounds in Balb-c mice over 14 d. Results: The optimized F5 formulation, selected based on desirability function (1.000), demonstrated superior properties: particle size 89.3±4.8 nm, zeta potential-26.8±1.0mV, and entrapment efficiencies of 86.4% and 89.2% for AP and TO respectively. F5 exhibited controlled drug release (81-82% over 12h) and excellent stability over 6 mo. In vivo studies revealed significantly enhanced wound healing with 96.2±2.1% contraction at day 14 compared to control (72.3±4.8%) and standard treatment (89.1±3.5%) (p<0.01). Conclusion: The optimized MSN formulation demonstrates promising wound healing potential with accelerated tissue regeneration compared to standard silver sulfadiazine treatment. These preclinical findings suggest potential for clinical development pending comprehensive safety, toxicity, and regulatory studies